Analysis and design of machine elements - Jiang, Wei, 1966- (John Wiley & Sons Singapore Pte. Ltd, 2019)
Incorporating Chinese, European, and International standards and units of measurement, this book presents a classic subject in an up-to-date manner with a strong emphasis on failure analysis and prevention-based machine element design. It presents concepts, principles, data, analyses, procedures, and decision-making techniques necessary to design safe, efficient, and workable machine elements. Design-centric and focused, the book will help students develop the ability to conceptualize designs from written requirements and to translate these design concepts into models and detailed manufacturing drawings. Presents a consistent approach to the design of different machine elements from failure analysis through strength analysis and structural design, which facilitates students' understanding, learning, and integration of analysis with design Fundamental theoretical topics such as mechanics, friction, wear and lubrication, and fluid mechanics are embedded in each chapter to illustrate design in practice Includes examples, exercises, review questions, design and practice problems, and CAD examples in each self-contained chapter to enhance learning Analysis and Design of Machine Elements is a design-centric textbook for advanced undergraduates majoring in Mechanical Engineering. Advanced students and engineers specializing in product design, vehicle engineering, power machinery, and engineering will also find it a useful reference and practical guide.